Digital infrared thermography of the scrotum, semen quality, serum testosterone levels in Nellore bulls (Bos taurus indicus) and their correlation with climatic factors - De Ruediger, Felipe Rydygier [UNESP]; Chacur, Marcelo George Mungai; Alves, Francisco Carlos Platzeck Estrella; Oba, Eunice [UNESP]; De Amorim Ramos, Alcides [UNESP] (Universidade Estadual de Londrina, 2016)
The objective was to study the relationship of climatic conditions with the temperature of the scrotum surface and sperm quality through digital infrared thermography in Nellore bulls, raised extensively. In six bulls held with scrotal thermography Flir E40® cameras, blood samples for serum testosterone and semen collection were taken by electroejaculation every 10 days, with six replications. Climatic factors: ambient temperature, relative humidity, dry globe temperature and temperature of the wet globe were recorded using a globe thermometer (InstruTemp®, ITWTG-2000). Thermal images of the scrotum were analyzed with the Flir Tools® software for the temperatures of scrotal surface, the right and left sides of the scrotum lap thirds: dorsal, middle and ventral testicles; and tails of the epididymis. The semen data and thermograms were submitted to ANOVA and Tukey's test at 5%. Pearson correlation was used for the surface temperatures of the scrotum, rectal temperature, quantitative and qualitative characteristics of semen and climatic factors. There was a positive correlation (P<0.05) for sperm motility x scrotal temperatures; sperm concentration x scrotal temperatures; climatic factors x rectal temperature. There was a negative correlation (P<0.05) between ambient temperature x sperm concentration. It was concluded that the temperature of the scrotum surface and climatic factors, temperature and humidity, influence the quality of semen. Thermography is recommended as a supplementary examination for reproductive evaluation of bulls.
Keywords: Climatic factors; Scrotal thermogram; Semen; Zebu bull